2009
DOI: 10.1002/ppap.200900032
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Polymerization of HMDSO with an Atmospheric Pressure Plasma Jet for Corrosion Protection of Aluminum and Low‐Adhesion Surfaces

Abstract: Thin functional films were deposited on aluminum with an atmospheric pressure plasma jet using hexamethyldisiloxane (HMDSO) as precursor. A high dynamic deposition rate on the order of 450 nm · m · min−1 was achieved. Composition and structure of the thin films show a strong dependence on the downstream location of the precursor injection. A 4 mm downstream shift of the precursor injection increases the carbon content in the thin film by a factor of 2.5, as indicated by XPS analysis and alters the degree of cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
65
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(70 citation statements)
references
References 38 publications
3
65
0
2
Order By: Relevance
“…A number of authors have previously described the operation of this atmospheric pressure plasma jet (APPJ) source [13][14][15][16][17]. A schematic diagram of the system is given in Figure 1, this illustrates how the blown arc is formed inside the arc cavity and ionized gas is expelled through the anode-nozzle [22 and 23].…”
Section: Equipment and Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of authors have previously described the operation of this atmospheric pressure plasma jet (APPJ) source [13][14][15][16][17]. A schematic diagram of the system is given in Figure 1, this illustrates how the blown arc is formed inside the arc cavity and ionized gas is expelled through the anode-nozzle [22 and 23].…”
Section: Equipment and Materialsmentioning
confidence: 99%
“…Amongst the plasma activation studies reported to-date with this source are those that aim to enhance the surface energy of polyethylene prior to adhesive bonding [13], adhesion improvement [6] and textile polymer treatments [14]. This source has also been used in the deposition of plasma polymerized coatings for gas barrier applications [15] and corrosion protection [16,17]. These papers have mainly focused on the process outcome as a function of anode-nozzle speeds relative to the treated surface.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, two reactive systems will be examined: one will use oxygen and hexamethyldisiloxane (case a) and a second will use oxygen and carbon dioxide (case b) as adsorptive species. The required activation energy will be provided by a plasma source [16,17] and a laser source [18], respectively. Surface modification with thin films composed of organosilicon-based plasma polymers was reported to be a promising approach for the corrosion protection of magnesium alloys, e.g.…”
mentioning
confidence: 99%
“…1). The reduction of the refractive index while thickness increased may indicate the presence of a developing porosity on the coating [155,156]. VÏ-l-3-Effect of deposition time on the wettability of PP-HMDSO coatings As mentioned before, our aim is to improve the stability of the PP-HMDSO coating.…”
Section: Vi-1-modification Of the Plasma Parametersmentioning
confidence: 99%